(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2019)
This short article surveys the possible origins of the rural conjunction manque (mas aunque, mas que, anque & mal que) and its distribution in Peninsular Spanish (thanks to data from the Linguistic Atlas of the Iberian Peninsula, ALPI) and American Spanish, and also offers ample documentation of all these forms.